3 - Weaponised and Displaced Women in Mass Atrocities and the RtoP - Idika-Kalu, Cecilia (Africa Development, 2021)
Terror groups, like al-Shabaab and Boko Haram, have emerged in recent years as key drivers of conflict in some African countries, generating mass casualties from routine suicide bomb attacks. The strategies of these groups include the increasing mobilisation and deployment of women in suicide bombing operations. At the same time, women have been among the most victimised by the activities of the terror groups, both as direct targets of attacks and as internally displaced people. The focus of this study is to discuss the twin dynamic by which women are both agents and victims of the terror groups. The study seeks to explore what existing knowledge tells us about possible future trends in the ‘weaponisation’ of women and mass atrocities. It also considers the place of Responsibility to Protect (R2P) tools in stemming the tide of the weaponisation of women. The nexus of gender, suicide bombing and displacement and what these mean for R2P are the sub-components of the analysis that underpins the article.